2013
DOI: 10.1002/iid3.14
|View full text |Cite
|
Sign up to set email alerts
|

C10X polymorphism in the CARD8 gene is associated with bacteraemia

Abstract: The NLRP3 inflammasome is an intracellular multi-protein complex that triggers caspase-1 mediated maturation of interleukin-1β (IL-1β); one of the most potent mediators of inflammation and a major cytokine produced during severe infections, like sepsis. However, the excessive cytokine levels seem to stage for tissue injury and organ failure, and high levels of IL-1β correlates with severity and mortality of sepsis. Instead, recent data suggest caspase-1 to function as a guardian against severe infections. CARD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…These results suggest that the host inflammatory state exerts a significant influence on the progression of cholesteatoma bone destruction. Increased severity of disease based on host inflammatory mutations for both NLRP3 and CARD8 has already been described for both Crohn disease and rheumatoid arthritis 12,14 . These results highlight the impact of the presence of the homozygous CARD8 mutant state in our study because the aforementioned studies demonstrated an impact on severity but not frequency of mutations compared to controls.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These results suggest that the host inflammatory state exerts a significant influence on the progression of cholesteatoma bone destruction. Increased severity of disease based on host inflammatory mutations for both NLRP3 and CARD8 has already been described for both Crohn disease and rheumatoid arthritis 12,14 . These results highlight the impact of the presence of the homozygous CARD8 mutant state in our study because the aforementioned studies demonstrated an impact on severity but not frequency of mutations compared to controls.…”
Section: Discussionsupporting
confidence: 79%
“…In this study, we focused on two commonly studied genetic variants: CARD8 C10X (accession number: rs2043211) and NLRP3 Q705K (rs35829419). The polymorphism C10X in CARD8 (rs2043211) causes a nonsense mutation in exon 5 that incapacitates inhibitory pathways of caspase‐1 activation, causing constitutive activation of downstream NLRP3 pathways and an increase in caspase‐1 production and cytokine release 12,13 . Meanwhile, the Q705K polymorphism in NLRP3 (rs35829419) achieves a similar phenotypic effect through a gain‐of‐function missense mutation in exon 3 14,15 …”
Section: Introductionmentioning
confidence: 99%
“…Such a termination mutation finally leads to a severely truncated protein. In addition to its reported association with inflammatory activity in RA patients, CARD8 p.C10X polymorphism also has associations with bacteriemia, Crohn's disease and ankylosing spondylitis …”
Section: Introductionmentioning
confidence: 99%
“…There is evidence for association of gout with functional variants in CARD8—multiplicative interaction with CARD8 would be consistent with a synergy of greater inflammasome activity, resulting from reduced CARD8 . Also, patients carrying polymorphism C10X in the CARD8 gene are at increased risk of developing bacteraemia and severe inflammation . All these data combined suggest that certain polymorphisms create inflammasomes with an increased basal activation state, which might provide a more favorable innate immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The nonsynonymous gain‐of‐function polymorphism NLRP3 rs35829419 (p. Q705K) leads to an overactive NLRP3 inflammasome, while caspase recruitment domain‐containing protein 8 (CARD8) rs2043211 (p. C10X) polymorphism encodes a truncated protein that does not inhibit the nuclear factor‐κB (NF‐κB) stimulation of inflammatory response . It was suggested that interaction between NLRP3 rs35829419 and CARD8 rs2043211 increases susceptibility to several inflammatory diseases and bacteriemia, but the results are inconclusive and have not been tested on patients with hip arthroplasty implants so far.…”
mentioning
confidence: 99%